La France : une délicate appropriation du genre - Caroline Jeanne (Genre & Histoire)
Since a few years, gender has a part in French medievists’ production. The emergence of this new resource is in line with women history, which was born in France in the 1970’, under the influence of George Duby or Christiane Klapisch-Zuber, for example. Nevertheless, in France, reluctances remain important, because of the difficult use of the word « genre », also because of a poor theoretical reflexion. For the moment, it emerges that gender is considered as a resource among others. Therefore, gender analysis revitalize several subjects: family, kinship, power or conflicts, and allow the emergence of new questionings, masculinity for example.